Caracterização e qualidade ambiental em dois fragmentos florestais na perspectiva da conservação de Alouatta guariba (HUMBOLDT, 1812) no interior do estado de São Paulo - Oliveira, Edson Montilha de (2009)
This study was accomplished in two forest s fragments with different environmental characteristics; the Parque Estadual do Morro do Diabo (PEMD), a Conservation Unit located at Pontal of Paranapanema, and the Água-Branca Farm Reserve (RPFAB), a fragment forest near to the of Araçatuba munipality. The objective was to research the environmental characterization and diagnosis of the two areas and to relate with the habitat quality for Alouatta guariba (Brown Howler Monkey). Tools of GIS (Geographical Information System) were used, letters IBGE s climbs 1:50.000, aerial pictures and images Google s to elaborate the thematic cartography of use and occupation of the land. The parameters used to evaluate the habitat quality were canopy covering, phytosociological analysis (vegetacional density and seed dispersion), diversity of dung beetles (Scarabaeidae), home-range area and populational density of A. guariba. The quantitative results among the studied areas were analyzed through the statistical programs EstimateS version 8.0, Systat version 11 and Instat version 3.05. To quantify the covering/opening of the hemispherical canopy pictures it was used a digital machine and the pixels in white were calculated through the program computational GLA (Gap Light analyzer) version 2.0. The home-range values were obtained on computational program Track Maker version 3.8 and also the Biotas 1.03 Alpha was used. The results of environmental characterization of studied areas revealed a fragile situation of the population of howler monkeys in function of the negative impacts of the urban growth in RPFAB. The values of canopy covering and vegetational density resulted insignificantly inferior to RPFAB when compared with PEMD, excepting the diversity of dung beetles that was larger in RPFAB. This fact is discussed through the argument of the entrance of dung beetles that are not characteristic of the forest environment and that came from existent pasture in the proximities. The home range and population density found of the two groups of monkeys are according to reviewed literature. For RPFAB the size of the home range (10,3 - 7,1 ha) it seems to be more influenced by the habitat quality, while for PEMD the size of the home range (11,7 - 8,0 ha) it seems to be influenced by the populational density of howler monkeys. The conservation of A. guariba in PEMD is guaranteed long term due to the size of the area and for treating of a Unit of Conservation. The presence of the species in RPFAB, however, is committed due to the surrounding soil use and occupation and for current intrinsic factors of the environmental quality of the habitat.